Green building: effeiciency and implementation principles in Ukraine - Nazvanov, D. (Ways to Improve Construction Efficiency, 2023)
The study of the principles and mechanisms of green building as a component of sustainable development is of great importance for modern science and practice. The article highlights key aspects of the implementation of green building in Ukraine, such as the adaptation of international standards, energy efficiency, economic incentives and increasing environmental awareness. In particular, the emphasis is on the integration of international certification systems (BREEAM, LEED, DGNB) into national building codes, which contributes to increasing the environmental safety and efficiency of construction projects. The impact of these standards on reducing energy consumption, optimizing the use of natural resources, and improving the environmental condition is described. The importance of developing a national green building standard in Ukraine is emphasized, which will contribute to creating environmentally safe living conditions and fostering innovative solutions in the construction sector. The works of Ukrainian and international scientists, which lay the foundation for the development of energy-efficient technologies and financial instruments (subsidies, tax breaks) in construction, are considered. focus on the impact of green building projects on ecosystems and public health, identifying their benefits for various groups: investors, regions, building owners. Among the concepts that have become the basis for the development of modern standards, the works of Amory Lovins ("Factor Four"), John Elkington ("Triple Approach"), William McDonough ("Cradle to Cradle") are highlighted. Norman Foster offers an interdisciplinary approach to designing environmentally efficient objects, integrating natural lighting, ventilation and materials with a low ecological footprint. The article provides a comparative table of characteristics of green and traditional construction, illustrating their environmental and economic efficiency. It points out the need to create a Ukrainian green construction standard that would meet the principles of sustainable development, promote environmental certification, and ensure sustainable development of regions even in the conditions of post-war reconstruction. Green construction in Ukraine needs to be activated through the development of a regulatory framework, the promotion of environmentally friendly materials, the improvement of professional training of specialists, and the popularization of the concept among consumers. This will create conditions for improving the quality of life, reducing the negative impact on the environment, and economic growth.